FORENSIC PRINCIPLES OF INTERROGATION TACTICS OF A VICTIM OF DOMESTIC VIOLENCE - Дрозд, В.Г. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2023)
The article analyzes the forensic principles of interrogation tactics for a victim of domestic violence and provides suggestions for optimizing the relevant process in the form of recommendations. The importance of carrying out the highest quality investigative (inquiry) actions in the pre-trial investigation of criminal offenses of violent content in general, as well as domestic violence, as one of the most dangerous types of illegal behavior in particular, is proved. In addition, attention is drawn to the fact that interrogation, among other investigative (inquiry) actions, is the most functionally applicable and universal investigative (inquiry) action, which allows to establish and detail a wide range of information about the criminal offense and the relevant subject of its commission. The purpose of the article is to analyze the principles of forensic tactics existing in science for interrogating a victim of domestic violence. This, in turn, necessitates the solution of such research problems as: 1. Delineation of the terminological component of the subject of a scientific article; 2. Detailing existing ideas about the tactics of interrogation of victims of domestic violence with the identification of the most outdated of them; 3. Identification of current trends in the principles of forensic tactics of interrogation of a victim of domestic violence and making proposals for discussion on ways to optimize the functioning of the relevant institution. The prospect of further scientific development of the relevant topics lies in the need to study the forensic tactics of interrogation of other persons participating in criminal proceedings for domestic violence.

Анотація. У статті проаналізовано криміналістичні засади тактики допиту особи, потерпілої від домашнього насильства, та наведено пропозиції щодо оптимізації відповідного процесу у формі рекомендацій. Доводиться важливість проведення якомога більш якісних слідчих (розшукових) дій у досудовому розслідуванні кримінальних правопорушень насильницького змісту загалом, а також домашнього насильства, як одного з найбільш небезпечних видів протиправної поведінки зокрема. Крім цього, звертається увага на те, що допит, серед інших слідчих (розшукових) дій є найбільш функціонально застосовною та універсальною слідчою (розшуковою) дією, що дозволяє встановити та деталізувати широкий спектр інформації про кримінальне правопорушення та відповідного суб’єкта його вчинення. Метою статті є аналіз існуючих у науці засад криміналістичної тактики допиту особи потерпілої від домашнього насильства. Це в свою чергу зумовлює необхідність розв’язання таких дослідницьких завдань, як: 1. Окреслення термінологічної складової тематики наукової статті; 2. Деталізації існуючих уявлень про тактику допиту осіб потерпілих від домашнього насильства з виокремленням найбільш застарілих із них; 3. Визначення сучасних тенденцій у засадах криміналістичної тактики проведення допиту особи потерпілої від домашнього насильства та винесення на обговорення пропозицій щодо шляхів оптимізації функціонування відповідного інституту. Перспектива подальшого наукового розвитку відповідної тематики полягає в необхідності дослідження криміналістичної тактики допиту інших осіб-учасників кримінального провадження щодо домашнього насильства.
Криміналістичні засади тактики допиту особи, потерпілої від домашнього насильства
Keywords: forensics; criminal procedure; violence; pre-trial investigation; domestic violence; interrogation tactics; European integration.; криміналістика; кримінальний процес; насильство; досудове розслідування; домашнє насильство; тактика допиту; європейська інтеграція.